Stereoselective Total Synthesis of (+)-Anamarine and 8-epi-(–)-Anamarine from d-Mannitol - Karnekanti, Rajender; Hanumaiah, Marumamula; Sharma, Gangavaram V. M. (Synthesis, 2015)
Stereoselective total synthesis of (+)-anamarine and the first synthesis of 8-epi-(–)-anamarine, its nonnatural diastereomer, were achieved from readily available d-mannitol. The key reactions involved were asymmetric dihydroxylation, cross-metathesis and ring-closing metathesis reactions. The approach is adoptable advantageously for the diversity-oriented synthesis of several related classes of natural products.
Keywords: (+)-anamarine; 8-epi-(–)-anamarine; d-mannitol; asymmetric dihydroxylation; cross-metathesis and ring-closing metathesis